The serotonin connection in ingestive disorders in women with and without irritable bowel syndrome (IBS) - Debbie Bloch; Anita D Stuart; H Gertie Pretorius (AOSIS, 1999)
This study compared women with lrritable Bowel Syndrome (IBS) and women without IBS, with regards to characteristics of indigestion disturbances, as measured by the Eating Disorder Inventory-2. A comparison between the two groups was also made of their blood-serotonin leveb. A sample group (N = 30) of women that suffer from IBSand~ac ontrol group (N = 28) completed the "lrritable bowel syndrome Client Questionnaire" and the "Eating Disorder Inventory-2". A part of the study attempted to determine if there is a significant difference between women with and wi!5out IBS with regard to the following subscales on the Eating Disorder Inventory-2: "Body Dissatisfaction", "Drive for Thinness", "Bulimia" and the "lntroceptive Awareness" subscale. The results show a statistical significant difference between the groups, as well as a statistical significant difference on the "Bulimia" subscale. A statistical significant difference between the groups was also shown with regard to the "introceptive Awareness" subscale. No differences were found with regard to the "Drive for Thinness" and the "Body Dissatisfaction" subscales. The results also did not show a statistical significant difference between the groups with regard to serotonin levels. Opsomming Die studie het vrouens met Prikkelbare Dermsindroom (PDS) en vrouens daarsonder vergelyk ten opsigte van kenmerke van die ingestie versteurings, soos gemeet deur die "Eating Disorder Inventory-2. 'n Vergelyking tussen die groepe ten opsigte van bloed-serotonien vlakke is ook getref. 'n Steekproei (N = 30) van vrouens wat aan PDS ly en 'n kontrolegroep (N = 28) het die "lrritable bowel syndrome Client Questionnaire" en die "Eating Disorder Inventory-2 voltooi. 'n Deel van die studie het gepoog om te bepaai of daar 'n beduidende verskil is tussen vrouens met en sonder PDS ten opsigte van die volgende subskale op die "Eating Disorder Inventory-2: "Body Dissatisfaction", "Drive for Thinness", "Bulimia" en die "lntroceptive Awareness" subskale. Die resultate dui op 'n statisties beduidende verskil tussen die groepe asook'n statisties beduidende verskil op die "Bulimia" subskaal. 'n Statisties beduidende verskil tussen die groepe is ook getoon ten opsigte van die "lntroceptive Awareness" subskaal. Geen verskille ten opsigte van die "Drive for Thinness" en die "Body Dissatisfaction" subskale is gevind nie. Die resultate toon ook geen statisties beduidende verskil tussen die groepe ten opsigte van serotonienvlakke nie.